2008
DOI: 10.1021/ja8017303
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in Mediating the Assembly of Alzheimer Amyloid-β Aβ16−22 Protofilaments

Abstract: The role of water in promoting the formation of protofilaments (the basic building blocks of amyloid fibrils) is investigated using fully atomic molecular dynamics simulations. Our model protofilament consists of two parallel β-sheets of Alzheimer Amyloid-β 16-22 peptides (Ac-K 16 -L 17 -V 18 -F 19 -F 20 -A 21 -E 22 -NH 2 ). Each sheet presents a distinct hydrophobic and hydrophilic face and together self-assemble to a stable protofilament with a core consisting of purely hydrophobic residues (L 17 ,F 19 ,A 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
245
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(262 citation statements)
references
References 58 publications
17
245
0
Order By: Relevance
“…db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water. As such, db's are pertinent to the α-β transition in amyloidogenesis [26,27], which can be affected by pressure [27,[74][75][76]. Atomic PMF simulations indicated that temperature lowers both the cm and the db [34,37,38,42] whereas pressure raises them [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water. As such, db's are pertinent to the α-β transition in amyloidogenesis [26,27], which can be affected by pressure [27,[74][75][76]. Atomic PMF simulations indicated that temperature lowers both the cm and the db [34,37,38,42] whereas pressure raises them [77].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, aside from protein core packing, hydrophobicity plays an important role in the conformation of small peptides. Understanding this role is useful, for example, to account for the emergence of enhanced β structures in proteins implicated in amyloid and prion diseases [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…These observations show that dehydration, resulting in the formation of the dry zipper region (4) as the monomer locks into the fibril lattice, is a key event in the growth of the amyloid fibrils. We surmise that interactions involving water must play an important role in the rate of fibril growth (41,42).…”
Section: Two-stage Dehydration and The Locking Process Are Coincidentmentioning
confidence: 91%
“…21 The growth process has also been probed by various computational studies that study how monomers of Aβ-fragments add to preformed oligomers. [22][23][24][25][26][27] For instance, Buchete and Hummer 28 proposed from all-atom molecular dynamics simulations of Aβ 40 a three-step process, where strong hydrophobic interactions align the C-terminal segments of the incoming peptide with such in the fibril encoura) Electronic mail: minghan2000@gmail.com. b) Electronic mail: hansmann@mtu.edu.…”
Section: Introductionmentioning
confidence: 99%